Borenium-Catalyzed ‘Chain Walking’ - Zhu, Zheng; Quan, Yangjian (Synlett, 2025)
‘Chain-walking’ chemistry, a catalytic process enabling the functionalization of remote positions in carbon chains, has traditionally relied on transition-metal catalysts to facilitate alkene isomerization and subsequent transformations. This Synpacts article reviews recent advancements in remote hydroboration via chain-walking pathways, highlighting transition-metal-catalyzed strategies for α-, β-, and terminal-selective borylation. Additionally, the isomerization of organoboron compounds and the emerging role of borenium species as transition-metal mimics in hydroboration and isomerization are discussed. In particular, we highlight our recent work on borenium-catalyzed ‘chain walking’ for remote functionalization, where we have unveiled a novel metal-free ‘functionalization-then-isomerization’ strategy.1 Introduction2 Background2.1 Transition-Metal-Catalyzed Remote Hydroboration2.2 Isomerization of Organoboron Compound2.3 Borenium-Catalyzed Hydroboration of Internal Alkenes and Isomerization3 Borenium-Catalyzed ‘Chain Walking’3.1 ‘Boron-Walking’ Strategy Design3.2 Reaction Scope3.3 Synthetic Application3.4 Mechanistic Study4 Summary and Outlook
Keywords: boron; chain walking; remote functionalization; borenium catalysis; site-selective